SINTESIS SURFAKTAN ALKIL POLIGLIKOSIDA (APG) BERBASIS DODEKANOL DAN HEKSADEKANOL DENGAN REAKTAN GLUKOSA CAIR 75% - Fina Uzwatania, Erliza Hambali, dan Ani Suryani (Jurnal Teknologi Industri Pertanian, 2017)
Alkyl poliglucosides (APG) is nonionic surfactant prepared from renewable raw materials based on carbohydrate and vegetable oils namely glucose and fatty alcohol. Glucose is the main raw material which is supplied the hydrophilic group, and fatty alcohol as hydrophobic group. APG was prepared using fatty alcohol varying in chain lengthsof C12 and C16 by two step methods (butanolysis and transasetalisation process). The catalyst of methyl ester sulfonic acid (MESA) was added. The effect of catalyst concentrations (1.5, 2, and 2.5%) was investigated.  The product evaluated for surface active properties. The chemical structures of the products were confirmed using fourier transform infrared spectroscopy (FTIR).The effects of fatty alcohol and concentration of catalyst were not significantly different to the pH and density. The result showed that reduction surface tension, reduction interfacial tension, and emulsion stability increased with increasing alkyl chain length and foam height decreases as the alkyl chain length increases. The best APG was obtained from C16 fatty alcohol (hexadecanol) and 2.5% of MESA catalyst, with the ability to reduce surface tensions at 1% concentration were 68.12%; the ability to reduce interfacial tensions of 98.14%, stability of emulsion of64%, foam height of 7.12%  and pH of 7.69.  Keywords: alkylpoliglycoside, fatty alcohol, glucose, surfactant